Kearifan Lokal Penguasa Daerah Menghadapi Liberalisasi Pendidikan "Upaya Kota Yogyakarta Meningkatkan Kualitas Pendidikan" - Herry Zudianto (Unisia, 2006)
The local government of Yogyakarta in increasing and maintaining the competitive advantage and, as the centre city of education is building supporting macro factors: layout, public education fasllities, regulation, and image (opini). Beside the factors ebove mention, in accordance with the outhority of city local government of Yogyakarta has made the effort to apply the quality education realization based on four indicators, those are the graduation quality, the quality of teaching and learning process, the quality of school service, and that of school atmosphere.